Nickel in the soybean resistance against Sclerotinia sclerotiorum infection - Fontes, Bianca Apolônio (2021)
White mold, caused by the fungus Sclerotinia sclerotiorum, is one of the most destructive diseases impacting soybean yield worldwide. Nickel (Ni) plays an essential role in the metabolism of higher plants because of its involvement in the catalytic process of several enzymes and as a constituent of many biomolecules. This study investigated the potential of spraying Ni to soybean plants to increase their resistance against white mold by accessing the photosynthetic performance (chlorophyll (Chl) a fluorescence parameters and photosynthetic pigments pools (chlorophylls a+b and carotenoids), the concentrations of malondialdehyde (MDA), total soluble phenolics (TSP), and lignin-thioglycolic acid (LTGA) derivatives as well the expression of genes encoding for phenylalanine ammonia-lyase (PAL1.1, PAL1.3, PAL2.1, and PAL3.1), chitinase (CHIA1), chalcone isomerase (CHI1B1), lipoxygenase (LOX7), metalloproteinase (MMP2), isochorismate synthase (ICS1 and ICS2), urease (URE), pathogenesis-related protein 1 (PR-1A), nitrate and nitrite reductase (NIR1-1 and INR-2), oxaloacetate acetylhydrolase (Oxalo), and an AP2/ERF type transcription factor (ERF3). The in vitro assay showed that Ni inhibited the mycelial growth of S. sclerotiorum. The higher foliar Ni concentration contributed to decrease white mold severity for Ni-sprayed plants which exhibited less MDA production, maintained great photosynthetic pigments concentration, and had their photosynthetic apparatus much more preserved than the plants non-sprayed with Ni. High concentrations of TSP and LTGA derivatives linked to higher expression of CHI1B1, PAL1.3, PAL2.1, PAL3.1, and PR-1A for Ni-sprayed plants contributed to their resistance against the white mold. Based on the present study results, it is plausible to conclude the potential of using Ni to enhance the resistance of soybean against white mold in the context of a more sustainable agriculture that prizes the mineral nutrition of plants. Keywords: Glycine max. Aternative Disease Control. Fungal Infection. Host defense Responses. Photosynthesis. Plant nutrition.